Differences in Walking Speed of SACH Foot And Single Axis Foot in Transtibial Prosthesis User - Suprayogi, Dody; Ningsih, Cica Tri Mandasari (Poltekkes Kemenkes Jakarta I, 2024)
Background: Lower limb amputation causes disruption of limb function, one of which is the ability to walk. One of the walking aids that can be used is a transtibial prosthesis. A transtibial prosthesis consists of a socket, shank and foot components. The choice of foot type and the use of a transtibial prosthesis is one of the factors that influence walking speed. SACH foot and single axis foot are the types of foot that are often used by prosthesis users Aims: To determine the difference in walking speed of SACH Foot and Single Axis Foot in transtibial prosthesis users. Method and Subjects: Using quantitative research, observational method with cross sectional design. The subjects of this research were users of transtibial prosthesis type SACH foot and single axis foot. The sample for this study consisted of 28 people. The measuring instruments used in this research are 10 MWT (Meter Walk Test). Results: Based on statistical tests, the results showed that there were differences in walking speed between SACH foot and single axis foot type transtibial prosthesis users. Where the p value <0.05 is 0.000 with an effect size of 0.81, which means it has a high or strong difference effect. Conclusion: There is a difference in walking speed, namely the walking speed of users of single axis foot transtibial prosthesis is faster than SACH foot. So, it is recommended to prefer using a single axis foot in users of transtibial prosthesis, especially at moderate activity levels. The limitations of this research are that there are not many subjects and the foot types are less diverse. Future research can be developed with other types of foot prosthesis and measurement of gait parameters